Prevalence of repeat faecal immunochemical testing in symptomatic patients attending primary care. (18th July 2022) - Johnstone, Mark S.; MacLeod, Campbell; Digby, Jayne; Al‐Azzawi, Yassir; Pang, Grace; Watson, Angus J. M.; Strachan, Judith; Mowat, Craig; McSorley, Stephen T.
Abstract: Aim: The faecal immunochemical test (FIT) for faecal haemoglobin (f‐Hb) helps determine the risk of colorectal cancer (CRC) and has been integrated into symptomatic referral pathways. 'Safety netting' advice includes considering referral for persistent symptoms, but no published data exists on repeated FITs. We aimed to examine the prevalence of serial FITs in primary care and CRC risk in these patients. Method: A multicentre, retrospective, observational study was conducted of patients with two or more consecutive f‐Hb results within a year from three Scottish Health Boards which utilize FIT in primary care. Cancer registry data ensured identification of CRC cases. Results: Overall, 135 396 FIT results were reviewed, of which 12 359 were serial results reported within 12 months (9.1%), derived from 5761 patients. Of these, 42 (0.7%) were diagnosed with CRC. A total of 3487 (60.5%) patients had two f‐Hb < 10 μg/g, 944 (16.4%) had f‐Hb ≥ 10 μg/g followed by <10 μg/g, 704 (12.2%) f‐Hb < 10 μg/g followed by ≥10 μg/g and 626 (10.9%) had two f‐Hb ≥ 10 μg/g. The CRC rate in each group was 0.1%, 0.4%, 1.4% and 4.0%, respectively. Seven hundred and thirty four patients submitted more than two FITs within a year. The likelihood of one or more f‐Hb ≥ 10 μg/g rose from 40.4% with two samples to 100% with six, while the CRC rate fell from 0.8% to 0%. Conclusion: Serial FITs within a year account for 9.1% of all results in our Boards. CRC prevalence amongst symptomatic patients with serial FIT is lower than in single‐FIT cohorts. Performing two FITs within a year for patients with persistent symptoms effectively acts as a safety net, while performing more than two within this timeframe is unlikely to be beneficial.